2007
DOI: 10.1016/j.envpol.2006.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lead on the sorption of 2,4,6-trichlorophenol on soil and peat

Abstract: Lead diminished the sorption of 2,4,6-trichlorophenol onto soil and peat. AbstractThe effect of lead on the sorption of 2,4,6-trichlorophenol (2,4,6-TCP) on soil and peat was investigated using a batch equilibration method. Lead markedly diminished the sorption of 2,4,6-TCP, and 2,4,6-TCP had little effect on lead sorption. Peat was a more effective adsorbent for 2,4,6-TCP than soil. The desorption hysteresis of 2,4,6-TCP verified the presence of high-energy sorption sites. Mechanisms of lead suppression effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 29 publications
(35 reference statements)
1
16
0
Order By: Relevance
“…2a and b, their adsorption on G and GO were almost independent of solution pH over the investigated pH range because both TCB and NAPH were nonionizable [3]. The adsorption of TCP decreased slightly over pH 2.0-6.0, and decreased rapidly at pH > 6.0, consistent to the adsorption of TCP on soil and peat [22]. Considering pKa value of TCP (6.15), it appears that the greater adsorption at low pH may be due to higher content of neutral TCP.…”
Section: 2supporting
confidence: 51%
“…2a and b, their adsorption on G and GO were almost independent of solution pH over the investigated pH range because both TCB and NAPH were nonionizable [3]. The adsorption of TCP decreased slightly over pH 2.0-6.0, and decreased rapidly at pH > 6.0, consistent to the adsorption of TCP on soil and peat [22]. Considering pKa value of TCP (6.15), it appears that the greater adsorption at low pH may be due to higher content of neutral TCP.…”
Section: 2supporting
confidence: 51%
“…Peat and soil were the same adsorbents used previously (16). A black chernozem soil (a clay loam Mollisol) was collected from the surface horizon (0-20 cm) in Heilongjiang Province, northeastern China.…”
Section: Methodsmentioning
confidence: 99%
“…However, contaminants often exist in mixtures in the environment, where they may affect each other's sorption. Heavy metals and organic contaminants coexist at many contaminated sites (Dai et al, 2007;Sprovieri et al, 2007), and coexisting heavy metal ions affect the adsorption of organic contaminants to soil, peat and charcoal (Pei et al, 2006(Pei et al, , 2007Chen et al, 2007). A few studies have been reported on competitive sorption between metals (Li et al, 2003b) or between organic contaminants on CNTs (Yang et al, 2006b).…”
Section: Introductionmentioning
confidence: 99%